THU0345 Defining Elementary Ultrasound Lesions in Gout. Preliminary Results of Delphi Consensus and Web-Exercise Reliability. (10th June 2014) - Gutierrez, M.; Smith, W.; Thiele, R.; Keen, H.; Kaeley, G.; Naredo, E.; Iagnocco, A.; Bruyn, G.; Balint, P.; Filippucci, E.; Mandl, P.; Kane, D.; et al.
Abstract : Objectives: To produce consensus-based definitions of the US elementary lesions and to test their inter and intra-reader reliability by a web-based exercise. Methods: The process included 2 steps: In the 1st first step, a written Delphi questionnaire was constructed on the basis of both data collected from the literature and the discussion results of OMERACT US members. This collated information resulted in 4 statements defining US lesions: double contour (DC), tophus, aggregate and erosion. The Delphi questionnaire was sent by email to 35 rheumatologist experts in US from 15 countries asking to rate their level of agreement or disagreement according to a 1-5 Likert scale (1=strongly disagree-5=strongly agree). The answers were summarized with mean scores. The 2nd step included the intra-reader reliability web-exercise. US images of both normal and gouty lesions, agreed upon in the Delphi process, were collected. A facilitator then constructed an electronic database of 110 images based on the 4 lesions. It was sent to the participants asking to read each image and determine the presence/absence of each score. A randomly selected group of 20 images was displayed twice to evaluate the intra-reader reliability. Results: 34 participants responded to the questionnaires. A consensus was reached after the third Delphi round. The definitions approved were: "DC": abnormal hyperechoic band over the superficial margin of the articular hyaline cartilage, independent of the angle of insonation and which may be either irregular or regular, continous or intermittent and can be distinguished from the cartilage interface sign; "tophus": A circumscribed, inhomogeneous, hyperechoic and/or hypoechoic aggregation (which may or may not generate posterior acoustic shadow) which may be surrounded by a small anechoic rim; "aggregates": heterogeneous hyperechoic foci that maintain their high degree of reflectivity even when the gain setting is minimized or the insonation angle is changed and which occasionally may generate posterior acoustic shadow; "erosions": an intra- and/or extra-articular discontinuity of the bone surface (visible in 2 perpendicular planes). The cumulative agreement for the final 4 definitions was: 91% for DC, 81% for tophus, 90% for aggregates, and 87% for erosion. Twenty participants completed the web exercise. The inter-reader kappa values for DC, tophus, aggregates, erosion were 0.98, 0.71, 0.54 and 0.85 respectively whereas the intra-reader was 0.84. Conclusions: This is the preliminary US consensus based definition of gout lesions and the first step to ensure a higher degree of homogeneity and comparability of results between studies and in daily practice. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5580